"Meine Zumutung, Hilfe mit der Feder zu leisten, hat mir viel Freude gemacht" - Matjašič Friš, Mateja (Studia Historica Slovenica, 2016)
Based on preserved correspondence this paper depicts the friendly relationship between the German writer Arthur Achleitner and Pavel Turner, Doctor of Law, educator, publicist and patron, who after retirement had settled permanently in Maribor. Achleitner and Turner met in the early spring of 1911 at the latest, most likely already in the autumn of 1910 when Achleitner visited the "Slovene Pohorje Mountains" in order to gather material for the novel he had been preparing. Turner made a great impression on Achleitner, the secret court councillor, who was also very knowledgeable and cosmopolitan since he had been moving between crowned heads on many European courts. 15 preserved letters that Achleitner wrote to Turner between 1913 and 1921 are a testimony to their friendly and mutually respectful relationship.
Keywords: biografije; pisma